Clostridium perfringens Types A and D Involved in Peracute Deaths in Goats Kept in Cholistan Ecosystem During Winter Season - Hussain, Riaz; Guangbin, Zhang; Abbas, Rao Zahid; Siddique, Abu Baker; Mohiuddin, Mudassar; Khan, Iahtasham; Rehman, Tauseef Ur; Khan, Ahrar (Frontiers in Veterinary Science, 2022)
Enterotoxaemia is a severe and peracute disease caused by Clostridium perfringens (C. perfringens) rendering high mortality leading to huge economic losses, especially in small ruminants. The bacterium induces peracute death in animals based on the rapid production of different lethal toxins. Mortality in three private herds of two breeds, i.e., Makhi-Cheeni and Beetal, and one non-descriptive (Teddy) herd were reared in the desert area of Bahawalpur, Pakistan. At necropsy, tissue samples for histopathology and intestinal contents for bacterial isolation and culture were collected. Following the standard procedure tissue slides were prepared. Multiplex PCR was used to identify toxinotypes using specific primers. Morbidity, mortality, and case-fatality in Makhi-Cheeni, Beetal, and Teddy goats caused by enterotoxaemia were 87.58, 75.81, and 76.11 %, respectively. Based on toxinotypes in the present outbreaks, C. perfringens type A (cpα = 20.7 %; cpα + cpβ2 = 11.2 %) and C. perfringens type D (cpα + cpβ2 + etx = 47.7 %; cpα + etx = 20.7%) were detected. Deaths due to C. perfringens type D (68.10 %) were significantly higher (p < 0.001) as compared to deaths by C. perfringens type A (34.90 %). Petechiation of serosal surfaces, hemorrhages of intestines, lungs, and liver were seen. Kidneys were soft and under the microscope, tubules were studded with erythrocytes. There was stunting and fusion in intestinal villi. From this study we concluded that endotoxemia can occur in any season, thus a proper vaccination schedule must be followed for the protection of small ruminants’ health.